A Deficiency of Donors or an Abundance of Barriers? Title IX Fundraising Challenges from the Perspective of Athletic Department Fundraisers - Matt R Huml; Katie M Brown; Mathew J Bergman (University of Kansas Libraries, 2020)
This paper explores how Title IX effects college athletic fundraising, particularly how athletic fundraisers creates an unfair environment for non-football and basketball programs. Using distributive justice as a theoretical lens, we examine the perspective of athletic department fundraisers working at NCAA, Power Five athletic departments. Interviews from participants gleaned insights into only meeting the minimum legal requirements of Title IX, fighting between non-revenue programs for remaining resources, elevated requirements for program success for non-football and basketball programs, and more. This paper aims at providing insight into a distinct context of fundraising, which often avoids Title IX scrutiny, but is the primary outlet for athletic departments to raise additional funds for their sport programs.